2013
DOI: 10.1186/1746-6148-9-215
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular heterogeneity among isolates of Yersinia ruckeri from rainbow trout (Oncorhynchus mykiss, Walbaum) in north west Germany

Abstract: BackgroundEnteric Redmouth Disease (ERM), caused by Yersinia ruckeri, is one of the most important infectious diseases in rainbow trout (Oncorhynchus mykiss) aquaculture in Europe. More recently, non-motile vaccine resistant isolates appear to have evolved and are causing disease problems throughout Europe, including Germany. The aim of this study was to analyse the variation of biochemical and molecular characteristics of Y. ruckeri isolates collected in north west Germany as a basis for strain differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
2
20
0
1
Order By: Relevance
“…Farms with a trading relationship (Huang et al 2013) to help trace the dissemination route of the Y. ruckeri isolates during recurrent disease outbreaks. This characterisation scheme revealed that in the majority of the farms, which were repeatedly sampled, bacteria from different TPs were found, and on several occasions, bacteria of different TPs were simultaneously present in the same farm.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Farms with a trading relationship (Huang et al 2013) to help trace the dissemination route of the Y. ruckeri isolates during recurrent disease outbreaks. This characterisation scheme revealed that in the majority of the farms, which were repeatedly sampled, bacteria from different TPs were found, and on several occasions, bacteria of different TPs were simultaneously present in the same farm.…”
Section: Discussionmentioning
confidence: 99%
“…During this field study, a total of 48 Y. ruckeri isolates were obtained from 16 of the 27 typing groups (TP) described by Huang et al (2013) (Table 3). The TPs were defined according to results obtained from biochemical (API 20 E) and molecular biological typing methods (repetitive PCR and PFGE macrorestriction analysis).…”
Section: Distribution Of Yersinia Ruckeri Isolatesmentioning
confidence: 99%
See 3 more Smart Citations